The Impact of Pelvic Floor Muscle Strengthening on the Functional State of Women Who Have Experienced OASIS After Childbirth - Atėnė Simanauskaitė; Justina Kačerauskienė; Dalia Regina Railaitė; Eglė Bartusevičienė (Medicina)
Background and Objectives: The primary objective of this study was to assess the impact of pelvic floor muscle (PFM) strengthening on the pelvic floor function in women who have experienced OASIS two years after delivery, and the secondary objective was to educate women about PFM strengthening and instruct them on the correct way to exercise. Methods and Materials: A prospective case-control study was conducted. The participants were divided into two groups: the case group (women who experienced OASIS) and the control group (women who did not experience perineal tears but had similar obstetric-related data to the case). Women were invited for a gynecological exam, PFM assessment, and consultation on PFM training. Women in the case group had three consultations, and women in the control group had two. Women were presented with four sets of questions about pre-pregnancy condition and questions related to UI and FI after delivery. Results were considered significant when p < 0.05. Results: OASIS were detected in 13 (0.4%) women in 2021. Risk factors for OASIS were found to be fetal macrosomia (p = 0.012), fetal occiput posterior position (p = 0.001), and epidural analgesia (p = 0.003). After one year of performing PFM strengthening exercises, some women in the study group exhibited stronger PFM contractions (p = 0.076), while others held the contracted PFM for a longer time (p = 0.133). UI affected women in the control group more often (p = 0.019). Two years after delivery, gas incontinence was mentioned significantly more frequently in the case group (p = 0.019). One year after initial consultation, gas incontinence was also more significantly common in the case group (p = 0.037). Conclusions: This study found that PFM strengthening exercises significantly improved pelvic floor function in women who experienced OASIS two years after delivery. Participants exhibited stronger PFM contractions and an increased ability to maintain these contractions. Women reported a better understanding of PFM exercises and proper techniques.